Partisipasi Masyarakat Dalam Pembangunan Desa di Desa Watesprojo Kecamatan Kemlagi Kabupaten Mojokerto - Akhmad Kusuma, Andika; Sidharta Arisandi, Rachman; Wijaya, Dian (Universitas Islam Majapahit, Indonesia, 2022)
Community participation really determines the success of planning or programs around the communityThe program also cannot be separated from community participation so that it can run well, community participation will be very much neededplanning or program, so that an activity can be carried out well and of course runs smoothly. This research aims tofind out the extent of community participation in development at the planning, implementation and monitoring stages of (physical) infrastructure inWatesprojo Village, Kemlagi District, Mojokerto Regency. The theory used is Yadav's Participation Theory which contains 1.) participationin Decision Making, 2.) Participation in Implementation of Activities, 3.) Participation in Monitoring and Evaluation, 4.) Participation inUtilization of Results. This research was conducted in a qualitative descriptive manner by collecting primary and secondary data. Selection of research informantsThis was done using purposive sampling, namely 6 people. The results of this research are 1.) The level of community participation seen from decision makingclassified as Low, because the community is only included in the Community Aspiration planning stage which is part of the Hamlet deliberation.Furthermore, at the Village Deliberation, the community is not involved, only the proposals come from the community. 2.) Level of community participationJudging from the implementation of development activities, it is considered good, because the community also took part in implementing the development welldonated in the form of skilled craftsmen or in the form of property (food consumption). 3.) The level of community participation can be seen from monitoringinfrastructure development is classified as Medium, because the community only criticizes verbally, not in writing to the Village LPM in the VillageWatersprojo.